2021
DOI: 10.1007/s11804-021-00227-w
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Emission Model for a Marine Diesel Engine with Data from Sea Operations

Abstract: In this study, a model is developed to simulate the dynamics of an internal combustion engine, and it is calibrated and validated against reliable experimental data, making it a tool that can effectively be adopted to conduct emission predictions. In this work, the Ricardo WAVE software is applied to the simulation of a particular marine diesel engine, a four-stroke engine used in the maritime field. Results from the bench tests are used for the calibration of the model. Finally, the calibration of the model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Surely, the main mover model can strongly characterize the complexity of the simulator as it can be faced with different approaches. Specific programming languages [20][21][22][23][24][25] or commercial software [26][27][28][29] can represent the engine behavior, with different levels of accuracy, according to the different purposes. On the contrary, the propeller is traditionally modeled by numerical tables, unless you want to describe further aspects, such as the dynamics of the rotation of the blades in the case of a controllable pitch propeller [30].…”
Section: Introductionmentioning
confidence: 99%
“…Surely, the main mover model can strongly characterize the complexity of the simulator as it can be faced with different approaches. Specific programming languages [20][21][22][23][24][25] or commercial software [26][27][28][29] can represent the engine behavior, with different levels of accuracy, according to the different purposes. On the contrary, the propeller is traditionally modeled by numerical tables, unless you want to describe further aspects, such as the dynamics of the rotation of the blades in the case of a controllable pitch propeller [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest statistics, in 2019 the port confirmed itself in third place in Italy, with 8 million passengers for cruise traffic and about 2 × 10 7 t of goods handled. 13,14 Compared to 2021, 2022 shows a +5.3% in the number of containers in TEU, a +14.0% in the number of docking ships, a +15.0% in the number of cruise passengers, and a +73% in the number of passengers. 15…”
Section: Portsmentioning
confidence: 95%
“…The analyzers of the noxious substances have been placed on board of an instrumented van located close to the cruise ship docks; in addition passive samplers were installed for almost all the rest of the port area to measure the sum of the contents of the main pollutants in the periods of tests and to obtain a scenario of the composition of the air in the port. For the pollutants considered, the hourly concentration averages have been obtained in Mocerino et al 14 and Prati et al 32 and the results are synthetically reported in Table 5 as mg/m 3 . Another campaign of the revelation of air quality in port was made by installing in a building of the port area a precise analyzer of the pollutants and measuring continuously for 15 days the composition of the air (see Figure 13).…”
Section: Experimental Campaign Carried Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamaris et al also employed a multi-zone combustion model to estimate the performance characteristics and the NOx emissions of a 12.5-MW largescale two-stroke diesel engine [24]. Mocerino et al developed a model using Ricardo WAVE software to simulate the dynamics and emissions of an internal combustion engine [25]. The model was employed as a tool for the evaluation of emissions, particularly NO.…”
Section: Introductionmentioning
confidence: 99%